2019
DOI: 10.1021/acs.langmuir.9b00462
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bubble Concentration on the in Vitro and in Vivo Performance of Highly Stable Lipid Shell-Stabilized Micro- and Nanoscale Ultrasound Contrast Agents

Abstract: Ultrasound (US) is a widely used diagnostic imaging tool because it is inexpensive, safe, portable, and broadly accessible. Ultrasound contrast agents (UCAs) are employed to enhance backscatter echo and improve imaging contrast. The most frequently utilized UCAs are echogenic bubbles made with a phospholipid or protein-stabilized hydrophobic gas core. While clinically utilized, applications of UCAs are often limited by rapid signal decay (<5 min) in vivo under typical ultrasound imaging protocols. Here, we rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
67
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 64 publications
(103 reference statements)
1
67
0
Order By: Relevance
“…Previous studies have suggested that altering the MB shell compositions is of great importance for the purpose of increasing the efficacy of drug delivery (Dicker et al, 2013;Abenojar et al, 2019). MB shells that have targeting ligands are especially attractive from the viewpoint of concentrating functional genes to a specific site for gene therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that altering the MB shell compositions is of great importance for the purpose of increasing the efficacy of drug delivery (Dicker et al, 2013;Abenojar et al, 2019). MB shells that have targeting ligands are especially attractive from the viewpoint of concentrating functional genes to a specific site for gene therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Nanobubbles with similar gas volumes to commercially available micron-sized UCAs, Definity and Optison, were shown to be more reliable for BBB opening, which could be a result of its smaller size and larger number of bubbles present [28]. A recent report by our group showed that at similar gas volumes, nanobubbles are less affected by changes in gas volume concentration compared to microbubbles [25].…”
Section: Introductionmentioning
confidence: 86%
“…Several reports have used total bubble gas volume as the main parameter in evaluating bubbles with the same shell components for ultrasound activity rather than the bubble count [23][24][25]. Microbubbles of different sizes evaluated with a similar gas volume were reported to show a similar circulation half-life, which suggests that gas volume may be a better predictor of UCA stability than bubble size [26].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations